Role of trace TEMPO as electron shuttle in enhancing chloroquine phosphate elimination in UV-LED-driven persulfate activation process. Issue 6 (December 2022) - Sun, Qiyuan; Fan, Yongjie; Yang, Jing; Lu, Zhilei; Xu, Zeping; Lai, Xingteng; Zheng, Yuyi; Cai, Kaicong; Wang, Feifeng
Abstract: Chloroquine Phosphate (CP) is an antiviral drug used for treatment of COVID-19. It is released into wastewater and eventually contaminates natural water. This study reports an effective homogeneous catalysis way for CP degradation by the 2, 2, 6, 6-Tetramethylpiperidine-N-oxyl (TEMPO) enhanced persulfate (PDS) activation under UVB-LEDs irradiation at 305 nm. TEMPO at a low concentration (0.1 μM) enhanced CP degradation in UV305 /PDS process in deionized water at different pHs, in different anions and different molecular weight dissolved organic matter solutions and in real surface water. The enhancement was verified to be attributed to the electron shuttle role of TEMPO, which promoted the yield of SO4 – by enhancing electron donating capacity of the reacting system. The degradation products of CP and their acute toxicities suggested that UV305 /PDS/TEMPO process has better performance on CP detoxification than UV305 /PDS process. This study provides a new way to tackle the challenge of pharmaceutical pollutions in homogeneous photocatalysis process for natural water and sewage restoration. Graphical Abstract: ga1 Highlights: UV305 /PDS/TEMPO process exhibits better CP detoxification than UV305 /PDS process. TEMPO promotes the yield of SO4 - by enhancing the electron transfer capacity. TEMPO enhancing CP degradation achieved in different pH and water matrix conditions.